Solution Combustion Synthesis of Cr2O3 Nanoparticles and Derived PVA/Cr2O3 Nanocomposites-Positron Annihilation Spectroscopic Study. (2016) - Prashanth, K.S; Mahesh, S.S; Nanda Prakash, M.B; Munirathnamma, L.M.; Ningaraju, S.; Ravikumar, H.B.; Somashekar, R.S; Nagabhushana, B.M
Abstract: Solution combustion based nanosize chromium oxide nanoparticles blended PVA/Cr2 O3 / NaCl nanocomposite thin films of various weight percentages were synthesized using solvent cast method. The FTIR and SEM results are in confirmation with XRD results indicating the formation of nanocomposites. Positron Life time spectroscopy (PALS) are used for the microstructural characterization in the (PVA)/ Cr2 O3 /NaCl polymer nanocomposites. The PALS results show that the free volume size and o-Ps lifetime (τ3 ) increases up to 4 wt% decreases after 6 wt% The decreased o-Ps lifetime (τ3 ) indicates the inhibition of o-Ps formation upon incorporation of Chromium Oxide nano particles into PVA matrix